2001
DOI: 10.1067/mcp.2001.115750
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion SR as an aid to smoking cessation in smokers treated previously with bupropion: A randomized placebo‐controlled study

Abstract: Bupropion SR is an effective medication for retreatment of smokers who have used bupropion SR previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0
5

Year Published

2003
2003
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(74 citation statements)
references
References 12 publications
(11 reference statements)
6
63
0
5
Order By: Relevance
“…In nine bupropion effectiveness studies examined, subjects received extensive counselling with seven studies reporting weekly brief (15 minutes or less) face-to-face counselling from research assistants, trial nurses and counsellor/psychologists. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] However, Australian studies have shown that smokers enrolled in smoking cessation pharmacotherapies are unlikely to actively participate in counselling. 44,45 The weight of research suggests that counselling does increase successful quit rates among smokers, therefore, if the additional expenditure is being spent on pharmacotherapies the additional marginal expenditure on telephone counselling may be money well spent.…”
Section: Discussionmentioning
confidence: 99%
“…In nine bupropion effectiveness studies examined, subjects received extensive counselling with seven studies reporting weekly brief (15 minutes or less) face-to-face counselling from research assistants, trial nurses and counsellor/psychologists. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] However, Australian studies have shown that smokers enrolled in smoking cessation pharmacotherapies are unlikely to actively participate in counselling. 44,45 The weight of research suggests that counselling does increase successful quit rates among smokers, therefore, if the additional expenditure is being spent on pharmacotherapies the additional marginal expenditure on telephone counselling may be money well spent.…”
Section: Discussionmentioning
confidence: 99%
“…However, although there exists behavioral and pharmacological treatments designed to promote smoking cessation, the great majority of abstinent smokers relapse after a quit attempt (Balfour and Fagerstrom 1996;Shiffman et al 1998;Fiore et al 2000), and almost all smokers who relapsed after initial cessation pharmacotherapy return to smoking after subsequent quit attempts (Tonnesen et al 1993;Gourlay et al 1995;Gonzales et al 2001). Therefore, the high rates of resumption of smoking after abstinence present a formidable challenge for the treatment of nicotine addiction.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the effects of bupropion sustained-release (SR), the only approved non-nicotinic medication, are thought to be mediated by dopaminergic mechanisms such as by blocking the reuptake of dopamine. [20][21][22][23] While several placebocontrolled trials of bupropion SR for smoking cessation have demonstrated its efficacy to promote smoking cessation 21,24,25 and a recent field trial has also shown the effectiveness of bupropion in actual practice, 26,27 only a minority of smokers treated with bupropion SR quit smoking for clinically meaningful periods (approximately 25-30% at 1 year follow-up).…”
Section: Introductionmentioning
confidence: 99%